Extracellular Vesicles as Mediators of Cellular Crosstalk Between Immune System and Kidney Graft - Quaglia, Marco; Dellepiane, Sergio; Guglielmetti, Gabriele; Merlotti, Guido; Castellano, Giuseppe; Cantaluppi, Vincenzo (Frontiers in Immunology, 2020)
Immune cell-derived extracellular vesicles (EVs) are known immune-modulators and exert a critical role in kidney transplantation (KTx). EV bioactive cargo includes graft antigens, costimulatory/inhibitory molecules, cytokines, growth factors and functional microRNAs (miRNAs) that modulate expression of recipient cell target genes. At cellular level, neutrophil- and macrophage-derived EVs exert respectively immunosuppressive and immune-stimulating effects on dendritic cells. Dendritic cell-derived EVs mediate alloantigen spreading among them and modulate antigen-presentation to T lymphocytes. At systemic level, EVs exert pleiotropic effects on complement and coagulation. Depending on their biogenesis, they can amplify complement activation, or shed complement-inhibitors and prevent cell lysis. Likewise, endothelial and platelet-derived EVs can exert pro-coagulant/pro-thrombotic effects but also promote endothelial survival and angiogenesis after ischemic injury. Kidney endothelial and tubular-derived EVs play a key-role in ischemia-reperfusion injury and, during the healing process, can trigger rejection by inducing both allo- and autoimmune responses. Endothelial EVs have pro-coagulant/pro-inflammatory effects and can release sequestered self-antigens, triggering a tissue-specific autoimmunity. Renal tubule-derived EVs shuttle pro-fibrotic mediators (TGFβ, miR21) to interstitial fibroblasts and modulate neutrophil and T-lymphocyte influx. These processes can lead to peritubular capillary rarefaction and interstitial fibrosis-tubular atrophy. Different EVs, including those from mesenchymal stromal cells, have been employed as therapeutic tool in experimental models of rejection and ischemia-reperfusion injury. These particles protect tubular and endothelial cells (by inhibition of apoptosis and inflammation-fibrogenesis and autophagy induction) and stimulate tissue regeneration (by triggering angiogenesis, cell proliferation and migration). Finally, urinary and serum EVs represent potential biomarkers for delayed graft function and acute rejection. In conclusion, EVs sustain an intricate cross talk between graft tissue and innate/adaptive immune systems. EVs play a major role in allorecognition, ischemia-reperfusion injury, auto- and alloimmunity, and are promising as biomarkers and therapeutic tools in KTx.